2019
DOI: 10.3390/ijms20122909
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of Glutamate Decarboxylase 65 Epitopes Reveals Dependency on Hydrophobic Amino Acids for Specific Interactions

Abstract: Characterization of multiple antibody epitopes has revealed the necessity of specific groups of amino acid residues for reactivity. This applies to the majority of antibody–antigen interactions, where especially charged and hydrophilic amino acids have been reported to be essential for antibody reactivity. This study describes thorough characterization of glutamic acid decarboxylase (GAD) 65 antigenic epitopes, an immunodominant autoantigen in type 1 diabetes (T1D). As linear epitopes are sparsely described fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
4
14
0
Order By: Relevance
“…The two peptide-specific CRT Abs recognized epitopes in the N-or C-terminal end of wt CRT, thus, the CRT mAbs reacted to the synthetic peptides as well as the native Ags (Figures 1 and 2), which is a crucial factor defining a well-functioning Ab [25][26][27]. Moreover, these findings indicate that the epitopes of the CRT mAbs are located in surface-accessible and flexible regions, which is typical for many Abs recognizing linear epitopes [40,42,43] and which is confirmed by comparison with published CRT structures [16,17].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The two peptide-specific CRT Abs recognized epitopes in the N-or C-terminal end of wt CRT, thus, the CRT mAbs reacted to the synthetic peptides as well as the native Ags (Figures 1 and 2), which is a crucial factor defining a well-functioning Ab [25][26][27]. Moreover, these findings indicate that the epitopes of the CRT mAbs are located in surface-accessible and flexible regions, which is typical for many Abs recognizing linear epitopes [40,42,43] and which is confirmed by comparison with published CRT structures [16,17].…”
Section: Discussionmentioning
confidence: 82%
“…Using overlapping peptides covering the complete CRT sequence, it was possible to identify the antigenic regions of mAb FMC 75 and mAb 16 (Figure 2), an approach which often has been applied with success for Ab characterization [42][43][44][45], as screening for Ab reactivity directly on the resin allows rapid identification [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease substrates γ-secretase TM peptide substrates/AD [41] Protease inhibitors HIV-protease inhibitors/HIV subtype C [42] Cell adhesion N-methylated TSP-1 peptides/CLL [43] Peptide antibody production P110/ mycoplasma genitalium, b-raf/ malignant melanoma [44,45] Epitope identification GAD/ diabetes, CENPF/ cancer, NMDAR/ encephalitis [34,46,47…”
Section: Researchmentioning
confidence: 99%
“…This technique is still the major method for MAb production, as described by Köhler and Milstein, even though minor modifications may be introduced, mainly in the screening phase, where an assay system identical to the end stage use should be used to avoid selection of clones with aberrant properties [94]. Upon successful screening and cloning, highly specific MAbs are obtained and the epitopes of these can be characterised with high precision, as illustrated by recent studies of MAbs to the glutamate decarboxylase isoforms 65 and 67, which were shown to recognise linear epitopes located in flexible structures [47,95]. Similar results have been obtained with many other MAbs, which verifies the stringent requirements for an optimal antibody-antigen interaction [33,46,96,97].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%